Specifics of Functioning the Phraseological Combination khochesh ne khochesh ‘like it or not’ - N. Y. Pilyugina (Научный диалог, 2017)
Specifics of the syntactic functions of phraseological combinations exemplified by the combination khochesh ne khochesh ‘like it or not’ is discussed. Novelty of research consists in that the studied combination is for the first time described in detail from the standpoint of the functional-semantic approach. The topicality of research is determined by happening in the Russian language active process of significant vocabulary being drawn in the composition of service vocabulary and, consequently, is determined by the need of expanded study of the syntactic functions of phraseological combinations as a means of formalizing syntactic relations. Description of studied combination in the dictionaries is presented. A review of scientific studies on syntactic phraseologization is made. The work focuses on the description of semantic structures in which there is the combination khochesh ne khochesh ‘like it or not’. The results of the analysis of the specific environment of combination within its scope in the text are shown. Also particular syntactic relationships, which are expressed by this combination, are commented. Special attention is paid to the analysis of explication of semantic structure of the text. It is emphasized that the analyzed combination is involved in the expression of subjective modality meanings. The author determines that the combination khochesh ne khochesh ‘like it or not’ indicates the presence of two situations, one of which is represented as necessary, having no alternative.